Melatonin alleviates circadian system disruption induced by chronic shifts of the light‐dark cycle in Octodon degus - Bano‐Otalora, Beatriz (John Wiley and Sons Inc., 2019)

(untitled) (J Pineal Res)
Modern 24‐h society lifestyle is associated with experiencing frequent shifts in the lighting conditions which can negatively impact human health. Here, we use the degus, a species exhibiting diurnal and nocturnal chronotypes, to: (a) assess the impact of chronic shifts of the light:dark (LD) cycle in the animal's physiology and behaviour and (b) test the therapeutic potential of melatonin in enhancing rhythmicity under these conditions. Degus were subjected to a “5d + 2d” LD‐shifting schedule for 19 weeks. This protocol aims to mimic lighting conditions experienced by humans during shift work: LD cycle was weekly delayed by 8h during 5 “working” days (Morning, Afternoon and Night schedule); during weekends (2 days), animals were kept under Morning schedule. After 9 weeks, melatonin was provided daily for 6h in the drinking water. The “5d + 2d” shifting LD schedule led to a disruption in wheel‐running activity (WRA) and body temperature (Tb) rhythms which manifested up to three separate periods in the circadian range. This chronodisruption was more evident in nocturnal than in diurnal degus, particularly during the Afternoon schedule when a phase misalignment between WRA and Tb rhythms appeared. Melatonin treatment and, to a lesser extent, water restriction enhanced the 24‐h component, suggesting a potential role in ameliorating the disruptive effects of shift work.